Analysis of the causes of accidents in Ghanaian Mines using Multiple Causation Model - Case Studies. - Gyebi, Frederick (University of Mines and Technology, 2019)
Mining companies in Ghana record series of injuries and fatalities each year. This research sought to analyse accident investigation records between 2012 and 2016 for two surface mines and two underground gold mines using a modified Multiple Causation Model. The causes of accidents were grouped into root causes and immediate causes. From the study, the root causes of accidents identified in the surface mines are: inadequate maintenance (38%); poor safety policies (31%); poor engineering design (14%); poor supervision (14%); and plant/equipment failure (2%). For the underground mines, the root causes are: poor safety policies (42%); poor supervision (22%); plant/equipment failure (20%); inadequate maintenance (10%); and poor engineering design (6%). The immediate causes identified in the surface mines are: poor judgment (18%); lack of skill (16%); poor risk assessments (15%); poor attitude/improper conduct (12%); body condition (12%); poor inspection/monitoring (10%); failure to follow Safe Operating Procedures (SOPs) (9%); failure to communicate hazard (7%); improper lifting methods (1%) and failure to secure (negligible). For the underground mines, the immediate causes are: poor attitude/improper conduct (22%); body condition (19%); poor risk assessments (19%); lack of skill (10%); failure to follow Safe Operating Procedures (SOPs) (8%); poor inspection/monitoring (8%); poor judgment (7%); and failure to communicate hazard (7%). It was observed that most accidents occur between 10:00 hrs -10:59 hrs GMT for the surface mines and 11:00 hrs – 11:59 hrs for the underground mines. It is recommended that management must ensure adequate maintenance regimes are put in place, must be committed to safety policies, employees should be given refresher training on hazard identification, evaluation and controls, supervisors must ensure that routine inspection/monitoring programmes are implemented, management must ensure that competent persons are employed for supervision and must ensure compliance with Regulations 44 and 291 of Minerals and Mining (Health, Safety and Technical) Regulations, 2012 (L.I. 2182).To maintain concentration and ease fatigue, employees should have the opportunity to take breaks from routine tasks.
ix, 69p. ill.
Keywords: Mining; Accidents; Safety issues